Psychosocial factors that influence HIV testing and condom use in men: A cross-cultural perspective - Roa, Antonio Milá (2021)
HIV infections continue to be a major public health issue worldwide. Two effective HIV prevention strategies are frequent HIV testing and consistent condom use. A growing body of literature has identified some psychosocial factors that influence the likelihood and consistency of HIV testing behavior and condom use in men, however little attention has been given to the role of cultural norms in shaping these associations. In an attempt to approach these findings from a cross-cultural perspective, we investigated the causal effects of three psychosocial factors previously associated with HIV testing and Condom Use in men across two culturally distinct European countries and tested whether these effects became more prominent in the country with the highest endorsement of traditional masculinity norms. More specifically, we examined whether Homonegativity, HIV Stigma, and HIV Knowledge were predictive of HIV testing and Condom Use among men in Portugal and Turkey, and whether these effects became more pronounced in the country with higher traditional masculinity norms or vice versa. As expected, Turkish participants displayed the highest endorsement of masculinity norms, however we only found that Homonegativity and HIV Stigma inversely predicted HIV testing. No significant effects were found between HIV Knowledge and HIV Testing., nor between either one of our independent variables and Condom Use. Although we found a significant interaction between HIV Stigma and country effect on HIV Testing, no other moderations were supported. Overall, these findings add to a growing literature on how psychosocial factors influence pro-health seeking behavior in European men. Future studies should aim to replicate these finding with a larger sample size.